Super-resolution FPGA implementation for medical imaging application - Wang, Peng (2014)
A board level lensless microfluidic imaging system is improved as part of the project. Cell detecting and counting algorithm is improved with more accuracy by using Matlab. New PCB is designed using PADS to adopt the image sensor with higher resolution (2.2µm * 2.2µm). More cell details can be retained through use of new system.